PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS SISWA KELAS KELAS IV MIS NW LENDANG ARA TAHUN PELAJARAN 2022/2023 - Muhammad Satriadi Muratama; Muhammad Ramdani Nur; Jaoharatis Tsani (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2022)
The problem that occurs in Social Sciences learning is the low learning outcomes of students. This is because the learning model applied is less effective. Based on the results of observations and interviews with class IV social studies teachers at MIS NW Lendang Ara, it was found that social studies learning outcomes were always low on social issues material. This can be seen from not achieving the KKM which should be 70, but is always below the KKM. As a result of observations, it appears that teachers have not implemented learning models in social studies learning, even though there are many innovative social studies learning models. The aim of this research is to determine the influence of the Project Based Learning learning model on the learning outcomes of class IV students in Social Sciences subjects at MIS NW Lendang Ara. This research is quantitative research with an experimental type, data collection using tests and questionnaires. The results of this research are that there is an influence of the project based learning model on the learning outcomes of class VI students in natural resources and economic activities. The average value of the experimental class students' learning outcomes was 79.2%, while the control class obtained an average of the results. student learning was 68.67%. In this way, the project based learning model through social studies subjects can be used by teachers in schools to improve student learning outcomes.